Global prevalence of E-cigarette use among students: Systematic review and meta-analysis - Natnael Atnafu Gebeyehu; Kelemu Abebe Gelaw; Yibeltal Assefa Atalay; Belete Gelaw Walle; Molalegn Mesele Gesese; Biruk Adie Admass; Belete Birhan; Awoke Elefachew Geberemariam; Biresaw Wassihun Alemu; Nathan Estifanos Shewangashaw; Kirubel Dagnaw Tegegne (PLoS ONE, 2025)
Background The growing use of e-cigarettes among students is a major public health concern. Yet, global data on its prevalence and associated risk factors remain limited. Therefore, this study aimed to estimate the global prevalence of e-cigarette use among students and identify key predictors influencing usage patterns. Methods A systematic review and meta-analysis were conducted using articles retrieved from databases including Science Direct, Scopus, EMBASE, Google Scholar, and PubMed, between August 15 and September 21, 2024. Data were extracted using Excel and analyzed with STATA version 14. Heterogeneity was assessed using the I 2 statistic, and publication bias was evaluated through forest plots and Begg and Egger’s tests. Subgroup analyses were conducted by geographic region, World Bank income classification, and level of education. A pooled odds ratio was calculated to identify predictors of e-cigarette use. Results A total of 40 studies with 654,853 student participants were included in the final analysis. The global prevalence of e-cigarette use among students was 22.65%. Usage varied significantly by region and demographic factors, with the highest rates observed in the Western Pacific (32.13%) and among high school students (33.62%). Students in high-income countries reported the highest usage (23.15%) as well. Key predictors of e-cigarette use included being male (AOR = 3.22), smoking conventional cigarettes (AOR = 5.35), and consuming alcohol (AOR = 3.14). Conclusion This meta-analysis reveals a high global prevalence of e-cigarette use among students, especially among high school males in high-income and Western Pacific regions, with strong associations to conventional cigarette smoking and alcohol use. Prioritize region-specific school based interventions targeting high-risk students particularly high school males in high-income countries to curb e-cigarette use and associated behaviors like smoking conventional cigarettes and alcohol consumption.